PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VII SMPN 2 KOTA SOLOK - Anggia Sukma Dewi (Jurnal Edukasi dan Penelitian Matematika, 2020)
Abstract – One of the basic abilities in mathematics is problem solving ability. But in the reality,   students mathematical problem solving ability is still low. One way to improve it is to apply Problem Based Learning (PBL) model. The purposes of this study is to analyze and describe the mathematical problem solving ability who learn to use the PBL model is better than the mathematical problem solving ability who learn to use conventional learning. The type of research is quasi experimental with Randomized Control Group Only Design and descriptive research. The study population was student of class VII SMPN 2 Kota Solok with a sample of class VII 8 and VII 9. The instument used was a test of mathematical problem solving ability. Based on the results obtained from the data analysis, it can be concluded that the mathematical problem solving ability of students who learn with PBL model is better than students who learn with conventional learning an the development of mathernatical problem solving ability of students learning with PBL model also increases. Keywords – Problem Based Learning, Mathematical Problem Solving Ability